SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS DEKSTOP PADA PT. ULTRA SAKTI - Eni Pudjiarti; Eka Puspitasari; Aprillia Ananda Septyawati (LPPM UNIVERSITAS BINA INSAN, 2019)
Inventory is very important in work activities or in a business entity, because inventory can be a benchmark of performance and cash flow of a company. If there is too much inventory turnover is not good, and vice versa if there is too little inventory it can hamper work activities, resulting in low yields and will affect the company's income. Because at PT Ultra Sakti, ATK Goods Inventory Management is still manual. Which causes the management and presentation of inventory data can be ineffective and inefficient, because it is very easy to make mistakes (Human Error) this results in the inventory process will be very bad, because it could be an excess or even a shortage of inventory processes. Therefore, the authors try to make an inventory system in order to help PT. Ultra Sakti in carrying out work activities to be more efficient and effective, in the presentation of data and data management. So that mistakes can be minimized. And the presentation of data can be utilized properly. Keywords— Information System Design, Inventory System